Peran Gubernur Jambi Untuk Mengontrol Kebijakan Pemerintah Daerah dalam Menanggulangi Covid 19 - Muhammad Jaelani (Universitas Batanghari Jambi, 2021)
In carrying out his duties as Governor, which is an extension of the central government in each province, the Jambi Governor must control the policies that have been imposed by the regional government at the city and district levels in tackling COVID-19. However, in reality until now the system of government in the regional government is still running its own government so it does not coordinate with the Governor as the leader in his regional province. This condition is certainly a problem in running the government system so that it needs to be studied more deeply related to the role of the Governor of Jambi. The subject matter studied in this study is related to the role of the Governor of Jambi in controlling local government policies. So in this case the research method used is a legislative and analytical approach. The research materials used are primary, secondary and tertiary legal materials and data collection techniques, namely literature studies and qualitative analysis techniques. The results of the discussion are that until now the role of the Governor of Jambi has not been carried out in controlling local government policies because the regional government in running its own government is still alone so that it lacks synergy in running the government system in order to cope with the spread of covid-19.